Isolation, Identification and Detection of Some Virulence Factors of Staphylococci in milk and cheese in Baghdad - Al-Khafaji, Marwa; Flayyih, May; Sabah, Majeed (Iraqi Journal of Science, 2024)
During 2011; 300 milk and white cheese samples were collected from Baghdad markets. Out of 200 staphylococcal isolates isolated from milk and white cheese samples, the predominant species was Staphylococcus aureus 97 isolates (48%), followed by S.chromogenes 82 (41%) and 21 (11%) S.epidermidis isolates. S. aureus isolates were DNase, coagulase, protease, urease, lipase, gelatinase and slime layer producers, other species were variable in the production of such virulence factors. S. chromogenes was the most prevalent isolated staphylococcal species from milk samples; while cheese samples contaminated mainly by S. aureus.